Transfusion Management of the Obstetrical Patient A Clinical Casebook (Springer International Publishing, 2018)
This clinical casebook covers transfusion medicine theory and its practical implications for the obstetrical hemorrhage patient through the presentation of cases on actively bleeding patients. Each case features a unique clinical scenario involving a bleeding patient and outlines different aspects of safe and effective transfusion support. The cases contain current evidence on the latest topics in the field, such as the use of antifibrinolytic agents and coagulation factor concentrates in the setting of massive obstetrical hemorrhage. In addition to the actively bleeding patient, the casebook includes other important management topics, including the role of plasma exchange in thrombotic microangiopathies during pregnancy; treatment of hyperhemolysis in a patient with hemoglobinopathy; and recommended management of patients with red cell antibodies found on prenatal testing. Other immunohematology topics such as post-natal management of an RhD negative woman for the prevention of hemolytic disease of the newborn due to anti-Rh(D) are included. Written by transfusion medicine, coagulation, obstetrical, and anesthesiology experts,Transfusion Management of the Obstetrical Patient: A Clinical Casebook is a concise yet comprehensive resource for anesthesiologists, obstetricians, pathologists, hematologists, and other practitioners who treat obstetrical hemorrhage patients.